Genetic variant of PRKAA1 and gastric cancer risk in an eastern Chinese population - Qiu, Li-Xin (Oncotarget, 2015)
Published data on the association between PRKAA1 rs13361707 T > C polymorphism and gastric cancer (GCa) susceptibility were inconclusive. To derive a more precise estimation of the association, we conducted a large-scale GCa study of 1,124 cases and 1,194 controls to confirm this association in an Eastern Chinese population. Our results showed that the C allele of PRKAA1 rs13361707 increased the GC risk in the study population [CT vs. TT, odds ratio (OR) = 1.72, 95% confidence interval (CI) = 1.40–2.12; CC vs. TT, OR = 2.15, 95%CI = 1.70–2.71; CT/CC vs. TT, OR = 1.86, 95%CI = 1.53–2.26; CC vs.TT/CT, OR = 1.49, 95%CI = 1.24–1.79]. In addition, the association of C allele with an increased GCa risk was still significant in subgroups, when stratified by age, sex, tumor site, drinking and smoking status. Moreover, the findings in the present study were validated by our further meta-analysis. In summary, these results indicated that the C allele of PRKAA1 rs13361707 was a low-penetrate risk factor for GCa.